CALCULATING THE OPTIMUM LEVEL OF RELIABILITY AND ANTI-SEISMIC REINFORCEMENT OF STRUCTURES OF BUILDINGS - H. R. Zajnulabidova; I. B. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Given problem optimization calculation of structures considering seismic hazard. Optimization conditions are presented based on probabilistic and economic criteria. For buildings with possible non-economic effects of a restriction on probability of failure, the amount of which is determined on the basis of the limitations of intangible losses. Seismic risk territories to evaluate as projected over the lifetime of a building influences with the relevant probabilities of occurrence and spectral parameters or in the form of calculation akselerogrammy. The feasibility of the methodology is shown in example Building with large bays with steel columns of the composite section dvutavrogo.